Genetic studies of Psammolestes tertius (Hemiptera : Reduviidae : Triatominae) using male genital morphology, morphometry, isoenzymes, and random amplified polymorphic DNA - Soares, RPP; Barbosa, S. E.; Borges, E. C.; Melo, T. A.; Romanha, A. J.; Dujardin, J. P.; Schofield, C. J.; Diotaiuti, L. (Springer, 2001)
Two Brazilian populations of Psammolestes tertius (Ceara and Minas Gerais) collected from thornbird nests (Furnariidae) were compared by male genital morphology, morphametry, isoenzymes, and random amplified polymorphic DNA (RAPD). Merle genitalia showed no difference between the populations. In contrast, morphometry, isoenzyme, and RAPD clearly distinguished the two populations. Possible mechanisms of dispersal and the origin of Psammolestes are discussed.
Keywords: Psammolestes tertius; isoenzymes; random amplified polymorphic DNA; morphometry; male genital morphology